Eating soya improves human memory - File, Sandra; Jarrett, Nicholas; Fluck, Emma; Duffy, Rosanna; Casey, Karen; Wiseman, Helen (Psychopharmacologia, 2001)
Soya foods are rich in isoflavone phytoestrogens with weak agonist activity at oestrogen receptors. Oestrogen treatment has been found to improve memory in men awaiting gender reassignment and in post-menopausal women. To examine the effects of supervised high versus low soya diets on attention, memory and frontal lobe function in young healthy adults of both sexes. Student volunteers were randomly allocated to receive, under supervision, a high soya (100 mg total isoflavones/day) or a low soya (0.5 mg total isoflavones/day) diet for 10 weeks. They received a battery of cognitive tests at baseline and then after 10 weeks of diet. Those receiving the high soya diet showed significant improvements in short-term (immediate recall of prose and 4-s delayed matching to sample of patterns) and long-term memory (picture recall after 20 min) and in mental flexibility (rule shifting and reversal). These improvements were found in males and females. In a letter fluency test and in a test of planning (Stockings of Cambridge), the high soya diet improved performance only in females. There was no effect of diet on tests of attention or in a category generation task. Those on the high soya diet rated themselves as more restrained and, after the tests of memory and attention, they became less tense than did those on the control diet. Significant cognitive improvements can arise from a relatively brief dietary intervention, and the improvements from a high soya diet are not restricted to women or to verbal tasks.